The perspective of justice in the thought of Imam Musa bin Jaafar (peace be upon him))) (Journal of the College of Basic Education, 2023)
The study of the biography of the Ahl al-Bayt, peace be upon them, is one of the basic building blocks of the ideological, intellectual, political and social ladder that Islam accepted as a method for correcting belief and regulating behavior, due to the great virtue they were known for and the distinguished position they achieved in the history of Islam.Many throughout history believe that the concept of justice is a vague concept that does not exist, and it cannot be fully achieved by any group or applied on the ground. Natural and moral law.The Prophet Muhammad, may God’s prayers and peace be upon him, and the family of his pure house were the most prestigious model in applying and achieving justice by achieving the truth, supporting the oppressed, and uprightness in the biography in word and deed. He embodied tolerance and interaction in a sincere and correct manner that no one lived up toHere, we dealt with the concept of justice in the thought of Imam Musa bin Jaafar, peace be upon them. Forbearance was one of the most prominent characteristics of Imam Musa, peace be upon him. He was a proverb in his dream and suppressing his anger. With favor, to erase the spirit of evil and selfishness from their souls